Environmental and genetic determinants of amphicarpy in Pisum fulvum, a wild relative of domesticated pea. (September 2020) - Hellwig, Timo; Flor, Almog; Saranga, Yehoshua; Coyne, Clarice J.; Main, Dorrie; Sherman, Amir; Ophir, Ron; Abbo, Shahal
Highlights: Amphicarpy is subject to a strong edaphic effect. Early flowering and modest biomass are associated with amphycarpic phenotypes. Higher prevalence of amphicarpy in drought prone territories subject to heavy grazing. Amphicarpy is a polygenetic trait likely to be affected by environmental stimuli. Abstract: Pisum fulvum is an annual legume native to Syria, Lebanon, Israel and Jordan. In certain locations, P. fulvum individuals were documented to display a reproductive dimorphism – amphicarpy, with both above and below ground flowers and pods. Herein we aimed to study the possible role of soil texture on amphicarpy in P. fulvum, to investigate the possible bio-climatic associations of P. fulvum amphicarpy and to identify genetic markers associated with this phenotype. A set of 127 germplasm accessions sampled across the Israeli distribution range of the species was phenotyped in two common garden nurseries. Land use and bioclimatic data were used to delineate the eco-geographic clustering of accession's sampling sites. Single nucleotide polymorphism (SNP) markers were employed in genome-wide association study to identify associated loci. Amphicarpy was subject to strong experimental site x genotype interaction with higher phenotypic expression in fine textured soil relative to sandy loam. Amphicarpy was more prevalent among accessions sampled in eastern Judea and Samaria and was weakly associated with early phenology and relatively modest above ground biomass production. Twelve SNP markers were significantly associated with amphicarpy, each explaining between 8 and 12 % of the phenotypic variation. In P. fulvum amphicarpy seems to be a polygenetic trait controlled by an array of genes that is likely to be affected by environmental stimuli. The probable selective advantage of the association between amphicarpy and early flowering is in line with its relative prevalence in drought prone territories subject to heavy grazing.